Les femmes dans le nom des rues bruxelloises. Topographie d’une minorisation - Nouria Ouali; Pierre Lannoy; Virginie Desamoury; Sandrine Guilleaume; Fanny Mayné; Sophie Merville; Charlotte Odier; Adèle Thébaux (Brussels Studies)
The article proposes an examination of odonyms in Brussels, i.e. the names of its streets, through the prism of gender. After a systematic survey of street names and the characteristics of the female figures honoured – which reveals a glaring imbalance between the female and male street names in Brussels (there are ten times fewer female odonyms than male odonyms in the Region) – the article analyses the practices and strategies used by municipal representatives to feminise street names and do justice to the memory of women through a transformation of the toponymy, among other things. On the one hand, it reveals the constraints linked to legislation, urban morphology and gender stereotypes which weigh on the undertaking to increase the number of female street names and, on the other hand, it analyses the action of elected representatives and the influence of feminist organisations which fight against the minoritisation of women in the materiality of the Brussels urban space.